SEORANG PENDERITA SINDROM NEFRITIK AKUT PASCA INFEKSI STREPTOKOKUS - Renny A Rena, Ni Made; Suwitra, Ketut (journal of internal medicine, 2012)
Acute nephritic syndrome is classically de! ned by symptoms of oliguria, oedem, hypertension and also urinalysis abnormality such as proteinuria less than 2 grams/day, hematuria, or ! nding of erytrocite silinder in the urine. The etiology of acute nephritic syndrome are disorders of primary glomerulopathy (idiopathic), glomerulopathy after infection, Disseminated Lupus Erythomatosus (DLE), vasculitis and hereditary nephritis (Alport syndrome). Acute nephritic syndrome is one of clinical manifestation of acute glomerulonephritis after streptococcal infection, which is in" lamation occur on tubulus and glomerular of the kidney, after streptococcal infection of skin or upper respratory tract. The most frequent cause by particular strain of hemolyticus streptococcus ß group A type 12. Herewith, we reported a case of acute glomerulonephritis after streptococcal infection with clinical manifestation acute neph! tic syndrome. A fourteen years old Balinese male patient found with anasarca oedem, oliguria and hematuria. Previous medical history with infection of throat 2 weeks before admitted to hospital. On physical examination, we found with Stage II hypertension, laboratory data shown urinalysis: hematuria and proteinuria, protein esbach 3.25 gram/liter/day, ASTO 200 IU/ml, ANA test negative and throat swab isolated Streptococcus viridans, alpha hemoliticus. Imaging data showed right pleural effusion and bilateral nephritis of the kidney. Patient gives a good respon to corticosteroid (metilprednisolone), diuretic and also ACE inhibitor
Keywords: nephritic, glomerulonephritis, streptococcal